Comprehensive transcriptomic and metabolomic analysis revealed drought tolerance regulatory pathways in upland cotton - Sun, Fenglei; Wang, Junhao; Geng, Shiwei; Liang, Yajun; Gong, Zhaolong; Yang, Ni; Qian, Shuaishuai; Zhang, Nala; Li, Xueyuan; Wang, Junduo; Zheng, Juyun (Frontiers in Plant Science, 2025)
Cotton is a kind of cash crop widely planted in arid and semi-arid areas. In this study, we performed multi-omics analysis of two drought resistant extreme materials, Yumian 4 and C460, under drought stress. Transcriptome analysis showed that DY (post-drought stress Yumian 4) had more differentially expressed genes than DC (post-drought stress C460), and there were 10247 DEGs in the two comparison groups. Metabolomics analysis identified 1766 metabolites, which were divided into 12 classes. The up-regulated metabolites mainly included lipid accumulation, phenylpropanoid biosynthesis, and flavonoids. The combined transcriptome and metabolome analysis highlighted the importance of phenylpropanoid biosynthesis in enhancing drought tolerance. Combining the two omics analysis, it was found that the enrichment pathway of differential genes and differential metabolites is mainly in the phenylpropane biosynthesis pathway, which contains 23 related candidate genes. In summary, the results of multi-omics analysis of the two extreme drought resistance cotton materials showed that they enhanced drought resistance by affecting phenylpropanoid biosynthesis pathways. Promote the accumulation of osmotic substances. The results further deepen our understanding of the molecular mechanism of drought tolerance in cotton and provide new insights for molecular breeding of cotton.